2014
DOI: 10.1177/070674371405901010
|View full text |Cite|
|
Sign up to set email alerts
|

An Updated Meta-Analysis of Randomized Controlled Evidence for the Effectiveness of Community Treatment Orders

Abstract: CTOs may not lead to significant differences in readmission, social functioning, or symptomatology, compared with standard care. Their use should be kept under review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 9 publications
2
32
2
2
Order By: Relevance
“…Around 35 outcome studies and three RCTs have investigated the effect on hospitalisation (rates, duration and time to readmission following placement on CTO) and community service usage. While non-randomised studies vary in quality and have inconsistent findings, all analyses of randomised data found no effect of CTOs [4, 79]. A meta-analysis of the patients from the three RCTs also found no effect on admissions or bed days or any improvement in psychiatric symptoms or global functioning [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 35 outcome studies and three RCTs have investigated the effect on hospitalisation (rates, duration and time to readmission following placement on CTO) and community service usage. While non-randomised studies vary in quality and have inconsistent findings, all analyses of randomised data found no effect of CTOs [4, 79]. A meta-analysis of the patients from the three RCTs also found no effect on admissions or bed days or any improvement in psychiatric symptoms or global functioning [7].…”
Section: Introductionmentioning
confidence: 99%
“…While non-randomised studies vary in quality and have inconsistent findings, all analyses of randomised data found no effect of CTOs [4, 79]. A meta-analysis of the patients from the three RCTs also found no effect on admissions or bed days or any improvement in psychiatric symptoms or global functioning [7]. Additionally, the OCTET trial testing the English regime [10] found no effect on subgroups [11] or any long-term (36 months) effect on hospital outcomes or on engagement with services [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of studies, however, investigate CTO outcomes with such a high level of rigour: 3 RCTs, 19-21 2 systematic reviews, 2,6 1 Cochrane review, 22 and 2 meta-analyses. 23,24 Most published outcome studies to date use nonrandomized methods. They are mainly controlled before-andafter (CBA) studies with matched non-CTO control subjects, uncontrolled before-and-after (UBA) studies where the patient's clinical status is compared before and after being placed on CTOs, or epidemiological studies that observe, but do not match, CTO and non-CTO populations.…”
Section: Types Of Outcome Studiesmentioning
confidence: 99%
“…The issue of care planning with consumers on CTOs is complex, with CTO legislation, service delivery models and resource availability all impacting upon implementation [14]. Significant concerns regarding the effectiveness and ethics of CTOs also exist with a recent review examining CTO effectiveness finding no differences in social functioning, quality of life or service use for individuals on CTOs compared to those receiving standard voluntary care [15]. Advocates for CTOs cite clinical improvement and being the ‘least restrictive’ treatment option as benefits [16, 17], whilst advocates against CTOs, often ex- service users, consider forced treatment a major barrier to collaborative, person-centred care [18].…”
Section: Introductionmentioning
confidence: 99%